Paul Williams [videorecording (DVD)] : still alive - Williams, Paul, 1940-; Kessler, Stephen (Virgil Films, 2013)
The charmingly self-narrated story of Stephen Kessler's lifelong obsession with the former superstar, and what happens when the nostalgic filmmaker finally catches up with him.